THE ROLE OF A PRINCIPAL IN DEVELOPING THE PROFESSIONALITY OF TEACHERS AT SMP NEGERI 10 IN TANJUNGBALAI - Ubat Ubat (JURNAL TARBIYAH, 2022)
This study aims to describe the planning, supervision, role, and actions of a school principal in developing teacher professionalism at SMP Negeri 10 in Tanjung Balai. This research follows qualitative research methods, and the triangulation technique is used to obtain the data through observation, interviews, and document studies. The results of this study indicate that the planning carried out by the principal is to create criteria for the acceptance of new staff, to create a teacher work program per quarter, and to save school funds. The supervision carried out is formative and summative model supervision, which is carried out periodically every week in the classroom by paying attention to the way the teacher teaches. Extrinsic motivation carried out by school principals in motivating their teachers is by praising the teachers, being respectful to teachers, listening to teacher complaints, following up on teacher complaints, and providing training in the IT field. Meanwhile, the intrinsic motivation is that when teachers cannot attend the training, the teachers can learn from their colleagues so that the teacher can continue to improve their abilities.